Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1182/blood-2006-08-042325
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent in-frame insertion in a CEBPA transactivation domain is a polymorphism rather than a mutation that does not affect gene expression profiling–based clustering of AML

Abstract: The transfusion of random platelets did result in a rise in platelet count (mean increments: 68 ϫ 10 9 /L and 87 ϫ 10 9 /L at day 0 and day 1, respectively), but this was significantly and consistently less over the lifespan of the transfused platelets than the mean increment seen with AC-Tx (116 ϫ 10 9 /L and 146 ϫ 10 9 /L on days 0 and 1, respectively). More importantly, the survival of the random platelets was only approximately half that of antigen-compatible platelets (T 1/2 of random platelets, 1.0 days;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…Although this particular insertion was a polymorphism, it is possible that a true mutation could be missed by a sequencing method alone due to low detection limit. 9,11,12 Taken together, our results suggest that the optimal approach for detecting CEBPA mutations in AML may be a combination of direct sequencing and a modified version of the fragment length analysis assay. Direct se-quencing is absolutely necessary to detect substitution mutations, but concurrent fragment length analysis offers greater sensitivity for detecting insertion or deletion mutations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although this particular insertion was a polymorphism, it is possible that a true mutation could be missed by a sequencing method alone due to low detection limit. 9,11,12 Taken together, our results suggest that the optimal approach for detecting CEBPA mutations in AML may be a combination of direct sequencing and a modified version of the fragment length analysis assay. Direct se-quencing is absolutely necessary to detect substitution mutations, but concurrent fragment length analysis offers greater sensitivity for detecting insertion or deletion mutations.…”
Section: Discussionmentioning
confidence: 71%
“…Samples from two patients had a TAD2 (1175 to 1180dup: ϩ6 bp) insertion previously reported as a polymorphism. 9,12,13 One polymorphism (patient G2) was initially detected only by fragment analysis. That case was classified as wild-type without a polymorphism by initial sequencing analysis, but the polymorphism was confirmed after sequencing more colonies.…”
Section: Characterization Of Cebpa Mutationsmentioning
confidence: 99%
“…The c.584-589dup ACCCGC leading to p.P194_H195dup (proline-histidine duplication) was initially reported as mutation but later found as a germline polymorphism (Frohling et al, 2004;Lin et al, 2005;Resende et al, 2007;Wouters et al, 2007). This polymorphism was reported in 3.1-39% in normal healthy controls (Pabst et al, 2001;Lin et al, 2005;Resende et al, 2007) and 3.2-20% in AML (Lin LI et al, 2005;Resende C et al, 2007;Leecharendkeat et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…12,16,19,20 In one study, the nt1175_1180dup was initially reported as a pathogenic mutation although later found to be a polymorphism as this alteration was present in the germ line and corresponds to the nonpathogenic polymorphism. 16,27 Some recent studies also detected this polymorphism in normal individuals and remission samples. 16 As the frequency of polymorphisms in this study was quite high and the numbers of cases with polymorphisms were enough to assess the clinical association, we decided to evaluate the clinical relevance of these polymorphisms.…”
Section: Discussionmentioning
confidence: 99%